2010
DOI: 10.4209/aaqr.2010.08.0070
|View full text |Cite
|
Sign up to set email alerts
|

The Hygric Performances of Moisture Adsorbing/Desorbing Building Materials

Abstract: Controlling indoor relative humidity is of great importance in the evaluation of thermal comfort and perceived air quality. This study aimed to develop a new mineral fiber board as an interior surface material with high capacity of moisture adsorption and desorption. A series of experiments were carried out in this study using an accurately controlled chamber, mock-up rooms, and real-scale test houses. The chamber test was conducted to measure the moisture adsorption and desorption content of the materials. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Chemical composition: X-ray fluorescence (XRF) analysis was performed with an automated RIX 2000 spectrometer [15]. The specific surface area, specific pore volume and average pore diameter (BJH method) of the samples were measured by N 2 adsorptiondesorption isotherms at 77 K using a surface area analyzer (Micromeritics, ASAP 2000).The adsorption/desorption efficiency were measured using the JIS A 1470 method [16], [17]. Table I presents the compositions of the waste fiberglass and waste catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical composition: X-ray fluorescence (XRF) analysis was performed with an automated RIX 2000 spectrometer [15]. The specific surface area, specific pore volume and average pore diameter (BJH method) of the samples were measured by N 2 adsorptiondesorption isotherms at 77 K using a surface area analyzer (Micromeritics, ASAP 2000).The adsorption/desorption efficiency were measured using the JIS A 1470 method [16], [17]. Table I presents the compositions of the waste fiberglass and waste catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was suspended in acetone, and droplets of the suspension were placed on a polymer micro grid supported on a Cu grid. The adsorption–desorption efficiency was measured using the JIS A 1470‐1 method . Before conducting moisture adsorption and desorption tests, the specimen was preconditioned inside the chamber with the ambient temperature of 23 ± 0.5°C and the relative humidity (RH) of 53% until the specimen reached a constant mass.…”
Section: Methodsmentioning
confidence: 99%
“…Tomita et al (2004) studied the humidity-control performance of silica-based hygroscopic materials based on equilibrium analysis and kinetics, and found that this material was very suitable for humidity control in airtight rooms. Kim et al (2010) developed a novel mineral fiber board, whose hygroscopic performance was three times more than the ordinary board and had an excellent performance in moderating indoor humidity. Feng et al (2018) tested the thermal and hygroscopic performance of the metal-organic frame material.…”
Section: Introductionmentioning
confidence: 99%